Aerodynamic study of vehicle drag based on bluff body - Mohamad Kamarul, Shamsuddin (2009)
The Ahmed'body represents a simplified geometry of 3D car model that can be used to study the flow characteristic in the .wake of vehicles.The main objective of this study is to analyze the drag of the Ahmed body with varying rear slant angle.The model occupied is 25°,30,and 350 rear slant angle where the-critical remarkable drag occur.The model,is simulated at the air, velocity, 40mls. The result is.validated using,previous study,(Ahmed, 1984)The CFD proved to bea useful technique since the compared reasonably well for both the current and the previous simulations. Concept of diffuser isapplied to the original model to check the drag, coefficient change.due to the different angle of diffuser. The tested diffluser an gle is .°' 1 Q° ° and coefficient change is analyzed.Major finding shows that the velocity flow underbody is become higher when adding the diffuser.The flows structure behind- the niodel was a separated region ovçr the slant and recirculation flows behind the model. The flow characteristic is influented by velocity change underbody,the observation indicates that the formation of vortices at the rear found to be c..iicwl , icopsistency iii p at.,is bringing to the drag losses, 2Q° The drag